Influencia de la presencia de calcio, cianuro, hierro, sodio y cobre en la determinación de oro en soluciones de percolación de minerales por el método de absorción atómica - Toledo Aguilar, Fernando (2005)
In the present work the way of how Calcium, Iron, Sodium, Copper and Cyanide interfere in the analysis of gold by atomic absorption for which two methods used in gold analysis by EAA (Atomic Absorption Spectrophotometry) were taken into account ) and dry analysis; knowing this, it was possible to simulate the real conditions of the analyzes in samples prepared in the laboratory. These samples consist of gold with a known concentration, in addition to the aforementioned pollutants, but always simulating the conditions of the real analyzes to have results of how these "interfering" interfere in the analysis of gold by atomic absorption. For these analyzes the Atomic Absorption Spectrophotometer was used: AAnalyst 300 by Perkin Elmer. As a theoretical framework, a review was made on spectrophotometry since atomic absorption spectroscopy (AAS) is the absorption spectroscopic method used to detect metal elements in the gaseous state. Normally, the procedure uses a flame to transform the analyte solutions into atoms in a gaseous state. The EAA is used mainly for quantitative analysis of metals in complex matrices; the limit of detection is, in favorable cases, of the order of parts per million to parts per billion. However, the detection interval is very variable, and depends both on the nature of the analyte and the matrix, and on the type of instrument. This technique has in common, with other spectroscopic techniques, that the instrument used consists of a radiation source, a sample holder, a monochromator and a detector. The phenomenon studied by the EAA can be divided into two main processes: The production of free atoms in the sample. The absorption of radiation from an external source by these atoms. In the flame, the absorption by free atoms (those atoms of the analyte devoid of its chemical environment, but not ionized) involves a transition of these atoms from the highly populated basal state to an excited electronic state. Issues were also written about quantification in spectrophotometry; Beer-Lambert's law as well as measurement errors that manifest themselves in spectrophotometry. It was also written about a spectrophotometer, its parts and the different types of spectrophotometries that exist; but of course focusing on the EAA that is the subject of this study. As regards the issues related to gold analysis, Atomic Absorption Methods for Gold are described in general, focusing on two quantitative methods that were chosen with the objective of simulating the real conditions of a gold analysis by EAA. Preliminary work and bibliographic referential allowed to outline the following sequence of work: Preparation of Patterns, then analyzed the two types of minerals that we had for this information of its composition to continue with the preparation of the study samples for each one of the methods of analyzes found in the bibliography. For method 1, solutions with a known amount of gold were prepared, adding the pollutants in different quantities to see the trend of the measurement and for method 2 solutions were prepared with a known quantity of gold and NaCN (this amount was determined in the literature) adding also the pollutants in different quantities to see the trend of the measurement, but always trying to simulate the real conditions of analysis. Once this preparation was finished, it was read in the spectrophotometer